COVID-19 in New Zealand: The Moderating Effect of Involvement on the Roles of Attitudes and Subjective Norms - Geoff Kaine; Vic Wright (COVID, 2024)
Popular theories that explain or predict behavioural intentions are based on people’s attitudes and subjective norms. Their application is based on the (often implicit) assumption that people regard a subject (e.g., preventing the spread of COVID-19) as sufficiently important for them to formulate stable attitudes and subjective norms about it. As this assumption rarely holds for all people, the influence of attitudes and subjective norms in determining behavioural intentions changes depending on the importance of the subject. In other words, importance has a moderating effect on the relationship between intentions, attitudes, and subjective norms. We hypothesise that, as importance declines, the influence on intentions of attitudes decreases and the influence of subjective norms increases. This has important implications for efforts to encourage the adoption of preventative behaviours in relation to COVID-19 because promotional strategies designed to modify attitudes differ markedly from those designed to modify subjective norms. We test this hypothesis by analysing three different large-scale surveys about people’s intentions, involvement, attitudes, and subjective norms regarding the spread of COVID-19 in New Zealand. The results support our hypothesis and highlight the importance of distinguishing between when the formation of behavioural intentions depends mainly on attitudes and when it depends mainly on subjective norms.